2020
DOI: 10.1016/j.ctro.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outcomes for patients with intermediate and high risk prostate cancer treated with low dose rate and high dose rate brachytherapy in combination with external beam radiotherapy

Abstract: Low dose rate brachytherapy High dose rate brachytherapy External beam radiotherapy a b s t r a c t Introduction: There is evidence to support use of external beam radiotherapy (EBRT) in combination with both low dose rate brachytherapy (LDR-EBRT) and high dose rate brachytherapy (HDR-EBRT) to treat intermediate and high risk prostate cancer. Methods: Men with intermediate and high risk prostate cancer treated using LDR-EBRT (treated between 1996 and 2007) and HDR-EBRT (treated between 2007 and 2012) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…At present, there are only two published studies comparing LDR vs. HDR boost in prostate cancer, both including patients of intermediate- and high-risk [ 24 , 25 ]. In King et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are only two published studies comparing LDR vs. HDR boost in prostate cancer, both including patients of intermediate- and high-risk [ 24 , 25 ]. In King et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a series of Slevin et al . [ 25 ] (287 patients of an institutional database), HDR boost was more than twice as likely to experience biochemical progression compared with LDR boost. At 5 years, bPFS was estimated to be 90.5% for the LDR-EBRT cohort, and 77.6% for the HDR-EBRT cohort.…”
Section: Discussionmentioning
confidence: 99%
“…HDR-BT (initially at a dose of 18 Gy in 3 fractions, subsequently 16 Gy in 2 fractions following a change in departmental protocol), was followed by EBRT within 2 weeks using IMRT (50. 4 Gy in 28 fractions). The results of this study showed that there was a significant decrease in radiation dose to the rectum throughout all rectal volumes, including expressed as an absolute volume (cc) or as a percentage of the contoured organ at risk.…”
Section: Dosimetrymentioning
confidence: 99%
“…Prostate brachytherapy (PBT) is a definitive treatment for prostate cancer [1,2]. Low-dose-rate (LDR) or highdose-rate (HDR) PBT can be used alone or in combination external beam radiotherapy (EBRT) to treat low, intermediate and high-risk prostate cancer [3][4][5][6]. Dose escalation is strongly linked to a reduction of biochemical and clinical failure and metastasis-free survival [7].…”
Section: Introductionmentioning
confidence: 99%
“…With great interest, we read the article by Slevin F et al published recently in the Clin Transl Radiat Oncol journal [1]. They compared the outcome between LDR boost and HDR boost for men with intermediate and high risk prostate cancer.…”
Section: To the Editormentioning
confidence: 99%